Pendugaan Erosi Tanah Berdasarkan Nilai Suseptibilitas Magnetik di Kenagarian Alahan Panjang, Kecamatan Lembah Gumanti, Kabupaten Solok, Sumatera Barat - Putri, Niken Rahayu; Budiman, Arif (Jurnal Fisika Unand, 2025)
A study has been conducted to estimate soil erosion based on magnetic susceptibility values in two areas, namely agricultural land and shrub land in Kanagarian Alahan Panjang, West Sumatra. Samples were taken at five points each at a depth of 10 cm, 50 cm and 100 cm located on a track with a length of 40 m. Measurements of magnetic susceptibility values were carried out using a Bartington Magnetic Susceptibility Meter with two frequencies, namely low frequency (klf) and high frequency (khf). These two measurement results were used to calculate the frequency-dependent susceptibility value (kfd). From the measurement results, it was obtained that the klf value for agricultural land ranged from 1925.3×10-5 SI to 2796.3×10-5 SI and shrub land ranged from 1041.3×10-5 SI to 2304.3×10-5 SI. These results indicate that the κlf value for all samples is classified as high which is controlled by ferrimagnetic minerals. Analysis of the klf and kfd values against depth shows that erosion has occurred on both land areas, where the area of land that has experienced erosion on the scrub land is smaller than on the agricultural land.